Tradisi Larangan Nikah Lusan Besan Perspektif Maqashid Syariah Menurut Pandangan MUI Langkat - Eva Nurhamiza (Journal Smart Law, 2023)
One of the traditions of the Javanese tribe is the ban on marrying lusan besan. Lusan besan marriage is a marriage in which the groom has been married twice and his future wife is still the first time. Their belief that bad things will happen if they ignore or forget about it. The prohibition of marriage according to Javanese custom is still widely held by most people where they believe that whoever violates this taboo in marriage then in the future his household will experience many problems and will have a bad impact on his extended family. From these problems, it is necessary to conduct research from the perspective of maqashid sharia by the fatwa authority, in this case, namely the Langkat MUI. This study aims to determine the tradition of the lusan besan marriage in the Javanese, the law in terms of the perspective of maqashid sharia in general and according to the Langkat MUI. The type of research used by the authors is qualitative research with a literature study approach. The data were collected using literature study techniques, interviews, and document research originating from fiqh books, interviews with the Langkat MUI, and other supporting sources. The data is then collected, reduced, presented and concluded. The results of the research are: first, a lusan besan marriage is a marriage where the groom has been married twice and his future wife is still the first time, which is prohibited in Javanese belief because of the assumption that disaster will befall the perpetrators' households; secondly, there is no legal basis for prohibiting the marriage of dozens of besan from the text; third, the Langkat MUI is of the view that the tradition of banning the marriage of lusan besan must be abandoned.